Molecular Characterisation of Diffuse Large B-cell Lymphoma in South Africa - Ramorola, Beatrice Relebogile (Department of Pathology, 2023)
Diffuse large B-cell lymphoma (DLBCL) is a highly heterogeneous and aggressive disease and is the most common subtype of non-Hodgkin lymphoma (NHL) in adults. Additionally, this subtype of lymphoma is also the most common in people infected with the Human Immunodeficiency virus (HIV), and the incidence has remained high despite the advent of Antiretroviral therapy (ART). About 30-40% of DLBCL patients' relapse, or are refractory to standard first-line therapy, and this is attributed to the high genetic and clinicopathological heterogeneity of the disease. Reports indicate that, among HIV-positive DLBCL patients, the response rate is even poorer. In low resourced settings, this is further aggravated by multiple factors including access to health facilities and gaps in communication. Recent genetic studies of DLBCL tumours allowed for the further subclassification of the ABC- and GCB- subtypes into at least 5 new groups, each with distinct genetic, molecular and clinicopathologic features, revealing potentially novel drivers of the disease. There is therefore a need to further understand the molecular pathology of these distinct subtypes, including within the context of HIV. The latter formed the basis of this study and used multiple approaches and methodologies, including immunophenotyping and mutational analysis of samples from local patient cohorts, as well as gene set enrichment analyses of publicly available DLBCL datasets. An analysis and comparison of immune cell populations in peripheral blood mononuclear cells, of HIV negative and HIV positive DLBCL patients was performed using flow cytometry (Chapter 3). The participants were newly diagnosed, chemotherapy naïve DLBCL patients. Some of the key observations were as follows: HIV-positive patients were diagnosed with DLBCL at significantly younger ages (75% under the age of 50 years), compared to the HIV negative DLBCL group. Furthermore, more extranodal disease and EBV infection were observed in the HIV-infected group, and both these factors are known to be indicative of more aggressive, advanced-stage disease. In general, cytopenias were observed in the DLBCL patient cohort, regardless of HIV status. Since most of the HIV infected patients were not adequately receiving antiretroviral therapy at the time of DLBCL diagnosis, the CD4+ helper T-cell population within this group was significantly reduced, in comparison to the HIVuninfected group. Interestingly, there was a significant difference in monocyte count between the two groups, with lower counts observed among the HIV-infected DLBCL patients. Additionally, increased activation of cytotoxic T-cells (CD8+CD38+), as well as lower mature cytolytic CD56dimCD16+ Natural Killer (NK) cells were observed in the HIV-positive DLBCL group. The prevalence of Myeloid differentiation primary response factor 88 (MYD88) L265P and Cluster of Differentiation 79B (CD79B) Y196 activating mutations were analysed in a cohort of archived ABC-DLBCL tumours (consisting of both HIV positives and negatives) (Chapter 4). Genomic DNA was isolated, the relevant genomic regions amplified by PCR, subjected to Sanger sequencing and then analysed and confirmed. The co-occurrence of both these mutations is characteristic of a newly described subset of DLBCL shown to have an inferior outcome. The prevalence of these mutations within an African population has as yet not been reported. The MYD88L265P mutation was detected in 26% of the amplified ABC-DLBCL tumours, while mutations at CD79BY196 were observed in 12% of the tumours. Co-occurrence of both these MYD88 and CD79B mutations were present in only 3 tumours, all of which were HIVnegative. Analysis of patient survival in relation to the mutations highlighted a trend showing that patients harbouring both mutations had worse overall survival. Interestingly, this pathogenic effect was more prominent for CD79B mutations, and this was comparable to the survival probability observed for HIV-positive patients. For the MYD88L265P mutation, an HIV positive status further decreased the survival probability. The final study presented in this thesis focused on investigating the expression and regulation of the Suppressor of cytokine signalling 1 (SOCS1) gene. SOCS1 has been recently reported to be a frequently altered gene in DLBCL, but molecular pathological studies on the role of SOCS1 in DLBCL are scarce. Using cell line models, basal SOCS1 gene and protein expression levels were assessed. In two DLBCL cell lines (SUDHL-4/GCB-DLBCL subtype and HBL-1/ABC-DLBCL subtype), SOCS1 expression was reduced at both the mRNA and protein levels when compared to control lymphoblastoid cell lines (LCLs), while in a third ABC-DLBCL cell line (U2932), results were varied. In silico analysis using the Cancer Genome Atlas (TCGA) database confirmed that SOCS1 is in the top 20 frequently mutated genes in DLBCL. Furthermore, these frequent mutations, which lead to reduced or low SOCS1 expression, are associated with DLBCL disease in its early stages (stages I and II) and with better survival estimates. In contrast, high expression of SOCS1 was associated with poor overall survival. This was further corroborated by gene set and pathway enrichment analyses, which highlighted factors involved in the enhancement of cancer-promoting processes such as proliferation, migration, invasion, and metastasis. Additionally, a previously reported association between the expression of methylation-related genes and SOCS1 expression was confirmed. Overall, these studies have uncovered novel insights into the pathology of DLBCL, including features unique to HIV-associated DLBCL. The implementation of a differential approach to the management of the disease, based on specific genetic and molecular features, should be explored. These findings support the importance of more studies, incorporating comprehensive genomic and molecular technologies, to continue to unravel the complex disease that is DLBCL.